A chemical window into the impact of RNAi silencing of the StNAC103 gene in potato tuber periderms: Soluble metabolites, suberized cell walls, and antibacterial defense. (October 2021) - Dastmalchi, Keyvan; Chira, Oseloka; Rodriguez, Mathiu Perez; Yoo, Barney; Serra, Olga; Figueras, Mercè; Stark, Ruth E.
Abstract: The growth and survival of terrestrial plants require control of their interactions with the environment, e.g., to defend against desiccation and microbial invasion. For major food crops, the protection conferred by the outer skins (periderm in potato) is essential to cultivation, storage, and marketing of the edible tubers and fruits. Potatoes are particularly vulnerable to bacterial infections due to their high content of water and susceptibility to mechanical wounding. Recently, both specific and conserved gene silencing ( StNAC103-RNAi and StNAC103-RNAi-c, respectively) were found to increase the load of wax and aliphatic suberin depolymerization products in tuber periderm, implicating this NAC gene as a repressor of the wax and suberin biosynthetic pathways. However, an important gap in our understanding of StNAC103 silencing concerns the metabolites produced in periderm cells as antimicrobial defense agents and potential building blocks of the deposited suberin biopolymer. In the current work, we have expanded prior studies on StNAC103 silenced lines by conducting comprehensive parallel analyses to profile changes in chemical constituents and antibacterial activity. Compositional analysis of the intact suberized cell walls using solid-state 13 C NMR (ssNMR) showed that NAC silencing produced an increase in the long-chain aliphatic groups deposited within the periderm cell walls. LC-MS of polar extracts revealed up-regulation of glycoalkaloids in both StNAC103- RNAi and StNAC103-RNAi-c native periderms but down-regulation of a phenolic amine in StNAC103-RNAi-c and a phenolic acid in StNAC103-RNAi native periderms. The nonpolar soluble metabolites identified using GC-MS included notably abundant long-chain alkane metabolites in both silenced samples. By coordinating the differentially accumulated soluble metabolites and the suberin depolymerization products with the ssNMR-based profiles for the periderm polymers, it was possible to obtain a holistic view of the chemical changes that result from StNAC103 gene silencing. Correspondingly, the chemical composition trends served as a backdrop to interpret trends in the chemical barrier defense function of native tuber periderms, which was found to be more robust for the nonpolar extracts. Graphical abstract: Image 1 Highlights: Potato StNAC103 silencing up-regulates glycoalkaloids in periderm polar extracts. A phenolic amine and a phenolic acid are down-regulated in various NAC-silenced polar extracts. NAC silencing up-regulates soluble long-chain alkanes and long-chain aliphatics within suberized cell walls. Nonpolar extracts from native periderms show antibacterial activity. The StNAC103 -RNAiperiderm extracts show highest antibacterial activity against E. coli.